ANALISIS USAHATANI CABAI MERAH PADA LAHAN SAWAH IRIGASI DI DESA KUMPUL REJO BUAY MADANG TIMUR OKU TIMUR - Munajat (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this research were to : (1) Calculate the amount of cost, income and income obtained from red chili farming in Kumpul Rejo Village, Buay Madang Timur District, OKU Timur Regency, (2) Analyze financial feasibility of red pepper farming in Kumpul Rejo Village East Buay Madang District of East OKU Regency. This research has been conducted in Kumpul Rejo Village, Buay Madang Timur Sub-district, East OKU Regency. Site selection is done purposively with the consideration that in the village there are farmers who cultivate red chilli by utilizing irrigated rice field. The study was conducted in April 2015. The study found that the total production cost incurred in the cultivation of red chili farming in Kumpul Rejo Village in a single production process with an average land area of 0.30 Ha was Rp 11,277,822, One production process amounting to Rp 36,033,750 so that the income received is Rp 24,755,928. The value of R / C ratio is 3.24 indicates the profitable pepper cultivation business. BEP value of production volume is 702 Kg, while BEP value of price is Rp 5,217 / Kg and ROI value is 224% indicating that farming system of red chili in Kumpul Rejo Village is feasible financially.